Optimization of operation in a waste recycling and composting plant - Kanat, G; Demir, A; Ozkaya, B; Bilgili, MS (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2004)
In Istanbul City a waste recycling and composting plant has been built as alternative for solid waste treatment and operated in test mode for more than one year. However, during test period, the plant could not been operated with high efficiency due to some management problems and un-separated waste collection. In this study, the operational optimization of the plant was investigated and, especially, waste collection areas and transfer stations have been found to be critical. New arrangement of the collection areas decreased the unsuitable waste portion from 17% to 5% and approximately 58% of oversized materials (> 80 mm) transferred to landfill areas could also be used at the plant. The annual economical loss resulting from inappropriate plant operation was estimated to be about 640 800 US dollars.
Keywords: operation; optimization; recycling; solid waste; Environmental Sciences & Ecology